2022
DOI: 10.1002/alz.12636
|View full text |Cite
|
Sign up to set email alerts
|

Daytime napping and Alzheimer's dementia: A potential bidirectional relationship

Abstract: Introduction: Daytime napping is frequently seen in older adults. The longitudinal relationship between daytime napping and cognitive aging is unknown. Methods:Using data from 1401 participants of the Rush Memory and Aging Project, we examined the longitudinal change of daytime napping inferred objectively by actigraphy, and the association with incident Alzheimer's dementia during up to 14-year follow-up.Results: Older adults tended to nap longer and more frequently with aging, while the progression of Alzhei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
45
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 47 publications
(76 reference statements)
6
45
3
Order By: Relevance
“…A recent study found that older adults tended to nap longer and more frequently with aging using objective actigraphy data. 27 The measurement difference and the age difference between their sample (81.42±7.47 years old) and ours (55.30±8.15 years old) might be the causes of this discrepancy. Thus, we conducted a simple test to investigate the association between baseline age and follow-up nap frequency change, as shown in Table S13.…”
Section: Discussioncontrasting
confidence: 52%
“…A recent study found that older adults tended to nap longer and more frequently with aging using objective actigraphy data. 27 The measurement difference and the age difference between their sample (81.42±7.47 years old) and ours (55.30±8.15 years old) might be the causes of this discrepancy. Thus, we conducted a simple test to investigate the association between baseline age and follow-up nap frequency change, as shown in Table S13.…”
Section: Discussioncontrasting
confidence: 52%
“…Meanwhile, a study showed that people with cognitive impairment had higher levels of CRP ( 49 ). In terms of nap duration, a study reported that excessive daytime naps and Alzheimer's dementia may have a bidirectional relationship or share common pathophysiological mechanisms ( 24 ). In addition, longer nap duration generally resulted in more sleep inertia ( 50 ), which resulted in decreased ability to think and perform ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that various factors are associated with cognitive frailty, such as physical activity ( 19 ) and nutrition ( 20 ). Moreover, many studies have shown that both physical frailty and cognitive impairment are associated with sleep status, including sleep quality ( 21 , 22 ) and nap duration ( 23 , 24 ). There are still insufficient studies related to the association between sleep status and cognitive frailty, except for a study on the association of nighttime sleep duration with cognitive frailty among community-dwelling older adults in 2021 ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings provide a hitherto underappreciated link between myelination and healthy sleep function, a connection that may be relevant to a range of neurological diseases. In mice, sleep fragmentation increases with age ( 45 ) and excessive sleep fragmentation is common in age-related disorders like Alzheimer’s disease ( 46 ), a disorder associated with deficits in oligodendrocytes and myelin ( 47 ). Numerous lines of evidence support that altered circadian biology is also significantly associated with MS prevalence.…”
Section: Discussionmentioning
confidence: 99%